DESDOBRO DE Eucalyptus grandis COM MOTOSSERRA, PARTE 1 – ANÁLISE DO DESEMPENHO OPERACIONAL - Djeison Cesar Batista (Ciência Florestal, 2013)
The aim of this work was to analyze the operational performance of Eucalyptus grandis W.Hill ex Maiden logs breakdown with chainsaw, taking into account small scale use, e.g., in small farms, using yield and operational efficiency as evaluation tools. The specific aim was to analyze the behavior of yield and operational efficiency in five diametric classes: 20.0-25.9cm, 26.0-28.9 cm, 29.0-31.9 cm, 32.0-34.9 cm and 35.0-41.0 cm. According to the results obtained, the chainsaw log breakdown had a satisfactory operational behavior, with average yield and operational efficiency of 58,5% and 0.55 m3/operator/h, respectively. However, the feasibility of such technique is restricted to small scale use. Diametric class 3 (29.0-31.9 cm) presented the best yield (66.6%) because it was the one that presented the best adequacy between log diameter and products. It is suggested for further researches the development of specific sawing patterns by diametric class, in addition to the reduction of class ranges, aiming the yield increase. The average breakdown time spent by log was the same for classes 3, 4 and 5, resulting that the latter presented the best operational efficiency (0.82 m3/operator/h).